Pelatihan Pembuatan Camilan Dendeng Ikan Tongkol Komo Bagi Kelompok Ibu-Ibu Binaan Koperasi Bhinneka Henggi Mas Kabupaten Fakfak - Maryati,; Ramadhana, Arga; Suloi, Andi Fitra (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2024)
Komo mackerel fish in Fakfak Regency is abundantly available and the price is also the cheapest among other fish. So far, there has been more education on nutmeg processing compared to fish processing. Bhinneka Henggi Mas Cooperative is a cooperative engaged in marketing that sells typical Fakfak gift hands where the products sold come from Cooperative Assisted Women. However, the cooperative-assisted mother's group still lacks creativity in fish processing due to low levels of education and knowledge. Therefore, the Community Service Team provided a solution in the form of training in making Komo mackerel jerky snacks for mothers assisted by the Henggi Mas Cooperative. This community service program provides benefits for Henggi Mas Cooperative Assisted Mothers in improving soft skills and science and technology. It can also be used as additional income because this product can be of high economic value. In general, the implementation of this service program includes three stages, theory presentation, practical assistance, and training evaluation. The mackerel jerky snack formula contains fresh komo mackerel, flour, spices, and water. After receiving training, the women the Henggi Mas Cooperative assisted have the knowledge and skills to process komo mackerel fish into jerky snack products. Keywords: Fish Jerky, Komo Mackerel Fish, Snack, Training